The Influence of Organizational Culture, OCB, Work Ethics on Employee Performance in PDAM Tirta Giri Nata Cirebon City - Tamara, Tia; Salsabila, Wafa; Sulistiyowati, Lisa Harry (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study investigates the influence of organizational culture, Organizational Citizenship Behavior (OCB), and Work Ethics on employee performance at PDAM Tirta Giri Nata Kota Cirebon. Design/Methodology/Approach: This study uses quantitative research methods. With questionnaire and observation data collection techniques. The sample used in this study was 158 respondents. The sampling technique was carried out by purposive sampling. With data analysis techniques using validity tests, reliability tests, classical assumption tests in the form of normality tests, multicollinearity tests, heteroskedasticity tests, determination tests, and hypothesis tests. The analysis method used is the Statistical Product and Service Solution (SPSS) Version 16.0 method. Findings: The findings show that organizational culture partially has no positive effect on employee performance, Organizational Citizenship Behavior (OCB) and Work Ethic partially have a positive and significant effect on employee performance. Simultaneously, the combined effect of organizational culture, OCB, and Work Ethic has a significant effect on the performance of PDAM Tirta Giri Nata Cirebon City employees with an influence of 36.3%. Research Limitations/Implications: One limitation of this study is the focus solely on employees of PDAM Tirta Giri Nata Kota Cirebon, which may limit the generalizability of the findings. Future research could explore other organizational contexts to enhance the generalizability of the results. Practical Implications: The findings suggest that fostering Organizational Citizenship Behavior (OCB) and nurturing a strong Work Ethics among employees can significantly enhance their performance in organizations such as PDAM Tirta Giri Nata Kota Cirebon. Originality/Value: This study contributes to the existing literature by examining the combined influence of organizational culture, OCB, and Work Ethics on employee performance, particularly in the context of a public utility company like PDAM Tirta Giri Nata Kota Cirebon. Paper Type: Research Paper Keyword: Organizational Culture, Organizational Citizenship Behavior (OCB), Work Ethics, Employee Performance, PDAM.